Inverse correlation of miR-196a and HOXB13 expression in Iraqi patients with prostate cancer: miR-196a Effects on HOXB13 in prostate cancer - Al-Khafaji, Hiba Muneer Abd-Alhassan; Khadum , Rehab M.; ouda , Sara Mohammed; Mohammed, Maryam Qasim (Cellular and Molecular Biology, 2025)
Prostate cancer (PCa), a significant health concern in aging men, is influenced by the HOXB13 gene, a key regulator of prostate development and cell differentiation. Dysregulation of HOXB13, including genetic variants and altered expression, is related to PCa risk and progression. Importantly, the expression of HOXB13 is modulated by microRNAs, particularly miR-196a. The miR-196a controls expression of genes via mRNA binding, causing degradation or inhibiting translation. It targets HOX genes, crucial for development, and exhibits variable activity in cancers, including PCa. Therefore, the interplay between PC, HOXB13, and miR-196a contributes to the understanding of the molecular basis of PCa and identifies potential therapeutic strategies. This study involved a case-control design, comprising 120 blood samples divided into 60 PCa patients and 60 controls. Molecular analyses were performed on these samples, involving total RNA extraction followed by purification via a commercial kit. Subsequently, complementary DNA was synthesized. A quantitative real-time polymerase chain reaction was used to measure the expression levels of the HOXB13 gene and miR-196a. Relative expression levels of both HOXB13 and miR-196a were determined using established quantification methodologies. Statistical analyses were conducted using SPSS and GraphPad Prism software. Our findings demonstrated a significant increase in HOXB13 gene expression (p≤0.01), specifically a fourfold elevation in PCa patients compared to healthy individuals. In contrast, miR-196a expression exhibited a significant decrease (p≤0.01), suggesting a potential inverse regulatory correlation with HOXB13. This study reveals a significant inverse correlation between HOXB13 and miR-196a expression in PCa patients. Specifically, the HOXB13 expression level was upregulated, while the miR-196a level was downregulated. These findings suggest that miR-196a may be used as a prospective tumor suppressor in PCa by negatively regulating HOXB13, thereby inhibiting cell proliferation and invasion. Consequently, miR-196a may emerge as a promising diagnostic molecular target for prostate cancer.